A retrospective analysis of preoperative staging modalities for oral squamous cell carcinoma. Issue 12 (December 2016) - Kähling, Ch.; Langguth, T.; Roller, F.; Kroll, T.; Krombach, G.; Knitschke, M.; Streckbein, Ph.; Howaldt, H.P.; Wilbrand, J.-F.
Abstract: Background: An accurate preoperative assessment of cervical lymph node status is a prerequisite for individually tailored cancer therapies in patients with oral squamous cell carcinoma. The detection of malignant spread and its treatment crucially influence the prognosis. The aim of the present study was to analyze the different staging modalities used among patients with a diagnosis of primary oral squamous cell carcinoma between 2008 and 2015. Material and methods: An analysis of preoperative staging findings, collected by clinical palpation, ultrasound, and computed tomography (CT), was performed. The results obtained were compared with the results of the final histopathological findings of the neck dissection specimens. A statistical analysis using McNemar's test was performed. Results: The sensitivity of CT for the detection of malignant cervical tumor spread was 74.5%. The ultrasound obtained a sensitivity of 60.8%. Both CT and ultrasound demonstrated significantly enhanced sensitivity compared to the clinical palpation with a sensitivity of 37.1%. No significant difference was observed between CT and ultrasound. A combination of different staging modalities increased the sensitivity significantly compared with ultrasound staging alone. No significant difference in sensitivity was found between the combined use of different staging modalities and CT staging alone. The highest sensitivity, of 80.0%, was obtained by a combination of all three staging modalities: clinical palpation, ultrasound and CT. Conclusions: The present study indicates that CT has an essential role in the preoperative staging of patients with oral squamous cell carcinoma. Its use not only significantly increases the sensitivity of cervical lymph node metastasis detection but also offers a preoperative assessment of local tumor spread and resection borders. An additional non-invasive cervical lymph node examination increases the sensitivity of the tumor staging process and reduces the risk of occult metastasis.